(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article highlights the importance and methods of effective organization of independent learning in foreign language teaching. The article discusses what benefits independent learning creates for students, how they manage their own learning process, and the possibilities of organizing learning in accordance with individual needs. The main ways of independent learning in foreign language learning are focused on goal-oriented planning, the use of Internet and mobile technologies, writing and speaking practices, a regular assessment system, and the role of teacher-mentors. The article emphasizes cooperation between students and teachers, personalized learning, and the use of modern technologies as important factors for the effective organization of independent learning. In conclusion, independent learning in foreign language learning is an important tool not only for increasing the student’s level of knowledge, but also for making him capable of self-management and development.